Implementation of Finite State Automata for 6-Axis Robot in the Screwing Process - Risfendra, Risfendra; Nursalam, Rapis; Purnama, Eko; Defri, Defri (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2025)
The screwing process is one of the important stages in the assembly of industrial products that requires high precision and time efficiency. This study implements Finite State Automata using Nondeterministic Finite Automata with the Mealy Machine model. The implementation of Finite State Automata on a 6-axis robot in the screwing process allows for better control, because each step in the process can be analyzed and programmed clearly. The system is controlled by a programmable logic controller that integrates a 6-axis robot, human machine interface, screwdriver, sensors, and pneumatic actuators. The screwing process is carried out using an automatic screwdriver, with the robot's movement following a logical sequence based on the Mealy Machine model state diagram. Each state represents the robot's operational steps, from taking tools, screws, to the screwing process. The study focuses on designing a system to move the robot according to the state diagram that activates the output based on the state transition to the input. The results show that the implementation of Finite State Automata is able to complete the screwing process consistently and repeatedly. This system also considers safe points to avoid collisions, thus supporting safety in the screwing process. The application of Finite State Automata on 6-axis robots is expected to provide convenience for users in understanding robot control in the screwing process and can be implemented according to industrial needs.